Programa computacional de ensino de habilidades auditivas. - Nascimento, Leandra Tabanez do (2007)
There is a great need to guarantee more access of the hearing impaired to hearing rehabilitation, specially their participation in auditory training programs (teaching of hearing behavior). Teaching computer programs which can be utilized by professionals, to guide and support the rehabilitation, and by the hearing impaired themselves and their family members, to perform home activities, are an alternative. This study aimed at applying and assessing a teaching program for the hearing recognition of words and sentences in the speech-to-noise ratio (SNR) of +10 dB. Four children with profound neurosensorial hearing impairment and one child presented mild to profound neurosensorial hearing impairment with neuropathy/auditory dyssynchrony, in the age range 7-9 yrs, able to read and write, all with pre-lingual hearing impairment and users of cochlear implant with full insertion of electrodes, presenting some ability in open-set speech recognition, were selected. The teaching procedure utilized the task known as matching to sample, that is, during the teaching tasks, a dictated word or sentence was presented as a model stimulus, and three written words or sentences were presented, as a comparison stimulus. The recognition of a set of 45 words and 45 sentences in the +10 dB SNR was taught, and to present the tasks, a modification of software Mestre and a notebook were used. The hearing recognition of dissyllabic words and sentences in silence and in the +10 dB SNR was assessed before and after the teaching. Four out of the five participants presented an increase in the indexes of words and phonemes recognition in silence and all participants presented an increase in the indexes of words and phonemes recognition, in the +10 dB SNR and in the indexes of sentence recognition, in silence and in the +10 dB SNR, after participating in the teaching program. Based on matching to sample, this program favored the emergence of the hearing behavior to recognize words and sentences, in the +10 dB SNR, in those participating in the program. The teaching program showed to be effective for the teaching of hearing abilities to children presented with pre-lingual hearing impairment, users of cochlear implant.